FAKTOR RESIKO ANEMIA PADA SISWI PONDOK PESANTREN - Rahayu Astuti; Ali Rosidi (Universitas Muhammadiyah Semarang, 2015)
The finding of several studies in Indonesia show that the anemia prevalence of adolescents remained high. Anemia on adolescents living in boarding schools showed a higher prevalence. The aim of the study analyzed risk factor of anemia on adolescents living in boarding schools. The study was conducted with analytic survey with cross-sectional design. Population were all female students from two boarding schools (pesantren) in Mranggen the District of Demak. The entire student also attending formal education in Madrasah Tsanawiyah. Sampling with the inclusion and exclusion criteria. The variables studied were hemoglobin levels were measured by Cyamethemoglobin, student identity data including age, class, medical history, number of children, father education and menarche status, and body mass index (BMI). Statistical analysis used univariate and bivariate analysis of the Chi Square test. The level of significance was 5%. The results showed that of 213 girls studied, who suffer from anemia 159 people (74,6%). Risk factor of anemia was age, class and menarche status. Schoolgirls aged 12-13 years the risk of anemia 3.435 times compared to female students aged 14-15 years. Female student from one class 7.202 times the risk of anemia compared to female students from two classes. While the number of children in the family, education of father and categories of body mass index (BMI) is not a risk factor for anemia in the boarding school students.Keywords: adolescents, boarding school, anemia, risk factor